(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The thesis contains information on the evolution of entrepreneurs participating in the innovation process and the organization of entrepreneurship, as well as the role and importance of entrepreneurship in foreign countries. The thesis is written on the basis of the methods of orthographic abstraction, grouping and systematic analysis. In the end, the author developed a system of unanimous conclusions and suggestions.